Optimization of solidifications/stabilization for petroleum-based waste using blended cement / Asna Mohd Zain - Asna, Mohd Zain (2013)
Petroleum waste is categorized as scheduled waste, one of the hazardous wastes that must be disposed at a licensed treatment plant. Refinery sludge produced in bulk quantity requires substantial cost for treatment. Toxic substance in the waste can be immobilized using stabilization and solidification method to reduce contaminant solubility and leachability using Portland cement as a main binder. Solidified waste with contaminants release in leachate below the standard levels can be disposed off on-site or recovered with limited utilization for construction materials. The petroleum sludge contained significant volatiles organics and oil and grease forming oily globules in thick sludge. Portland cement mainly composed of tricalcium silicate and dicalcium silicate. The cement to the sludge and water to cement ratios of 8 and 0.45 accordingly was used as the design parameters to investigate the effect of cement replacement materials at 5, 10 and 15 % weight. The cement replacement materials are condensed silica fume (CSF), fly ash (FA), activated carbon (AC), rice husk ash (RHA) and metakaolin (MK). RHA was the best binder of all cement replacement materials with 5 % weight achieved optimum strength of 28.34 N/mm2. Similarly, other binders’ strengths were optimized at 5 % weight. The increase in permeable porosity was in tandem with the rise of cement to the sludge ratio, while a contradictory effect was observed in the lower water to cement ratio. Isostrength peak was maximized at higher water to cement ratio of 0.45 in tandems with porosity but reversing effect occurs at the lower ratio. Prominent isostrength peak was observed with the inclusion of 5 % weight of cement replacement material for all binders. Inclusion of 5 % weight CSF, FA and MK in solidified sludge have resulted in the increased of micropore volume. Average pore size was also increased with cement replacement materials except FA. Minimum metals were leached out from of solidified sludge and solidified sludge with cement replacement materials as determined by TCLP U.S. EPA SW-846 Method 1311. All toxic metals were below the applicable standard. Semi-dynamic leaching test of ANS 16.1 was employed as long term landfill leaching to determine leaching rate, diffusion coefficient and leachability index. Leaching rate of metals signify the diffusion leaching. Dynamic leaching of metal diffusion was pH control. Leaching achieved equilibrium at pH 9.5 whereby acetate ions are dominating the solution in reducing redox potential. Leachability indexes of most metal were above 6 as a guidance limit for landfill application of the monolith. Leaching mechanisms were governed by wash-off and diffusion. All semi-dynamic metals released were below the applicable standard. The solidified OPC sludge has exhibited ettringite and amorphous C-S-H surface. Inclusion of sludge has changed the surface into more C-S-H and less ettringite with calcium as the main element. Cement replacement material has affected reduction in the calcium content due to the concurrent rise in carbon. Pozzolanic reaction in the solidified sludge has caused the reduction in silica. The main crystal in the solidified sludge was rhombohedron calcite, which were formed by carbonation reaction of C-S-H and C-H with CO2 in the cement hydration product. Thermogravimetry analysis of solidified sludge has exhibited the active pozzolanic reaction at temperature of 300 to 500C shown by the weight loss of Ca(OH)2. Another significant weight loss was due to decomposition of carbonation product at temperature 500 to 800C. Solidified sludge contained linear or branched aliphatic hydrocarbon. The reaction of silica and carboxylic acid with hydrocarbon formed cyclic siloxane and acid ester. 1H-NMR exhibits alkyl group’s hydrogen in the solidified sludge. Similar 1H groups were present in the leachate but inclusive of aromatic proton. 13C-NMR indicates the presence of straight chain alkane’s carbon in the solidified sludge. As a conclusion, the stabilization/solidification of petroleum sludge containing metal and organic volatiles with Portland cement is effective by the formation of low organic and metal leachability with moderate unconfined compressive. The leachability levels were below the toxicity characteristic of Environmental Quality Act 2009 and U.S.EPA standard. The solidified sludge unconfined compressive strength was above the satisfactory U.S.EPA of 0.34 MPa limit.